A decision-making formula for value engineering applications in the Sri Lankan construction industry. Issue 1 (3rd April 2017) - Karunasena, Gayani; Rajagalgoda Gamage, Kosala
Abstract : Purpose: The construction industry in many developing countries is reluctant to apply value engineering (VE) due to uncertainty of outcomes. The purpose of this paper is to examine the existing practices of VE techniques and make recommendations to organisations and national construction regulatory bodies, to standardise VE practices. A decision-making formula is introduced to determine profitability of VE applications prior to implementation. Design/methodology/approach: A broad literature review and six case study projects that applied VE were selected. Thirty-nine semi-structured interviews were conducted to gather data within cases. Six expert interviews were conducted as confirmatory interviews to clarify and validate research outcome. Content analysis and cognitive mapping were used to analyse data among case studies. Findings: Application, knowledge and experience on VE techniques among construction professionals are unsatisfactory. Recommendations include reducing contractor's design responsibility, introducing proper VE guidelines and statutory regulations. A framework is introduced to assist authorities to standardise application of VE techniques. A decision-making formula is suggested to determine margins of contractor's portion due to VE techniques and original profits gained. Originality/value: The formula can be used as a decision-making tool by construction industry practitioners to determine successfulness of proposed VE techniques, and the proposed framework can be used to guide construction professional bodies to standardise VE practices.